English Students’ Perceptions in Participating the Praktisi Mengajar Program - Ulfah, Lisnani; Isnaniah, Isnaniah; Yuliani, Novi Dwi (English Teaching and Linguistics Journal (ETLiJ), 2024)
Praktisi Mengajar Program is a part of Merdeka Belajar Kampus Merdeka (MBKM) initiative. In this study, researcher examines students’ perception of the Praktisi Mengajar Program. The study aims to determine the students’ views on the importance of the program, its advantages and disadvantages, and how they adapt to it. This research is a qualitative study that collects data by distributing questionnaires to English education students at Nahdlatul Ulama University of South Kalimantan, who have participated in the campus teaching program. This research was conducted during the 2023/2024 academic year. The sample for this study consisted of 15 English education students at Nahdlatul Ulama University, South Kalimantan. Data analysis was performed using the data model proposed by Sugiyono (2019). Initially, the researcher distributed questionnaires to the students. Subsequently, the collected data were re-examined and presented in the form of tables, bar charts, and percentages. The results of the study showed that 72% of students considered the program important, 62% felt the program was sufficient, 68% saw a positive impact, and 65% were able to adapt well to the program. Overall, the average positive assessment was 67%, indicating that the Praktisi Mengajar Program had a beneficial impact on students.